PENINGKATAN KEWASPADAAN COVID 19 MELALUI EDUKASI DAN BERBAGI PENGALAMAN - Dyan Fitri Nugraha; Tuti Alawiyah (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
The increase in covid-19 cases in the community, especially in South Kalimantan, attacks all age groups, including teenagers. The penetration of the health protocol campaign is still lacking in increasing public awareness so that they could take an active role in implementing health protocols for themselves and everyone around. Therefore, there is a need for another approach in a more flexible format for the community, especially teenagers, in sharing experiences from covid-19 survivors, as well as the need for a comprehensive understanding of the impact of covid-19 on individuals and families. The campaign must continue to be innovative and consistent. Teenagers become objects of community service due to the high intensity of internet use in social media so that they can provide positive information to their surroundings. This program aims to increase awareness of covid 19 through education and sharing experiences from covid-19 survivors in a format adapted to the character of partners. The method used is a survey of partner conditions, implementation of activities, and evaluation of activities. This activity results in a significant increase in partner knowledge regarding covid-19. --- Peningkatan kasus Covid-19 di masyarakat, terutama Kalimantan Selatan menyerang semua lini usia, termasuk remaja. Penetrasi kampanye protokol kesehatan dirasa masih kurang meningkatkan kepedulian masyarakat agar berperan aktif dalam menerapkan protokol kesehatan bagi diri dan orang sekitarnya. Oleh karena itu perlu adanya pendekatan lain dalam format yang lebih santai kepada masyarakat terutama remaja dalam berbagi pengalaman dari penyintas Covid-19, serta butuhnya pemahaman komprehensif mengenai dampak penyakit Covid-19 bagi pribadi ataupun keluarga. Kampanye harus terus dilakukan secara inovatif dan konsisten. Remaja menjadi objek pengabdian kepada masyarakat dikarenakan tingginya intensitas penggunaan internet dalam bermedia sosial, sehingga dapat memberikan informasi positif kepada sekitarnya. Tujuan dari program ini adalah meningkatkan kewaspadaan Covid-19 melalui edukasi dan berbagi pengalaman dari penyintas Covid-19 dengan format yang disesuaikan dengan karakter mitra. Metode yang digunakan adalah survei kondisi mitra, pelaksanaan kegiatan, dan evaluasi kegiatan. Hasil dari kegiatan ini adalah terjadi peningkatkan pengetahuan mitra terkait Covid-19 secara signifikan.